2019
DOI: 10.1523/jneurosci.0914-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Electrophysiological Signals Reveals the Temporal Properties of Visuomotor Computations for Precision Grips

Abstract: The frontoparietal networks underlying grasping movements have been extensively studied, especially using fMRI. Accordingly, whereas much is known about their cortical locus much less is known about the temporal dynamics of visuomotor transformations. Here, we show that multivariate EEG analysis allows for detailed insights into the time course of visual and visuomotor computations of precision grasps. Male and female human participants first previewed one of several objects and, upon its reappearance, reached… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 95 publications
(100 reference statements)
3
12
0
Order By: Relevance
“…This is possible by running multivariate analysis correlating individual participants' trial-by-trial fluctuations in neural activity associated with specific kinematics (Gu, Wood, Gribble, & Corneil, 2016) and eye-movements. Although similar explorations have been conducted, the current methods improve spatial resolution previously obtained with combined EEG & motor tracking (Amengual et al, 2014;Guo et al, 2019;Sburlea & Muller-Putz, 2018), and temporal resolution obtained with combined fMRI and motor tracking (Budisavljevic et al, 2017;Di Bono et al, 2017;Filimon, Nelson, Huang, & Sereno, 2009). Furthermore, correlating individual neural signature variations to individual kinematic profiles will provide an intrinsic link between neural population activity and specific aspects of motor control that is currently lacking (Lehky & Sereno, 2019).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This is possible by running multivariate analysis correlating individual participants' trial-by-trial fluctuations in neural activity associated with specific kinematics (Gu, Wood, Gribble, & Corneil, 2016) and eye-movements. Although similar explorations have been conducted, the current methods improve spatial resolution previously obtained with combined EEG & motor tracking (Amengual et al, 2014;Guo et al, 2019;Sburlea & Muller-Putz, 2018), and temporal resolution obtained with combined fMRI and motor tracking (Budisavljevic et al, 2017;Di Bono et al, 2017;Filimon, Nelson, Huang, & Sereno, 2009). Furthermore, correlating individual neural signature variations to individual kinematic profiles will provide an intrinsic link between neural population activity and specific aspects of motor control that is currently lacking (Lehky & Sereno, 2019).…”
Section: Discussionmentioning
confidence: 74%
“…This will provide a more accurate multimodal view of grasping processes (Betti, Castiello, & Begliomini, 2021). Subsequently, associated brain analysis may classify neural signatures into those more related to visual properties, hand movements, or eye movements, and outline which factors influence their individual contributions and interactions (Guo, Nestor, Nemrodov, Frost, & Niemeier, 2019). Overall, these methods improve previous visuomotor research in three main ways.…”
Section: Discussionmentioning
confidence: 99%
“…They also provide a valuable complement for EEG studies that reveal temporal coding with even finer temporal resolution but poorer spatial resolution. An EEG study by (Guo et al, 2019) showed that grasp orientation (defined by instruction rather than object attributes) can be classified during both a visual preview and action execution, with similar representations between the two phases; moreover, their most informative electrodes were over left caudal parietal cortex, though source localization indicated diverse potential sources (that may include cIPS, SPL, and EBA).…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the current study was to investigate how isolated and sequential actions unfold differently on a moment-to-moment basis. The temporal unfolding of brain activation during actions has been largely overlooked (or only studied with EEG, without localizing the specific brain regions involved, e.g., Guo et al, 2019). Most studies that have used multivoxel pattern analysis (MVPA) to investigate hand actions have averaged data within time bins for planning and execution (e.g., Gallivan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Turella et al (2016) identified action planning processes ;750 ms after object presentation and upstream from effector-related processes. Guo et al (2019) revealed the time course of object shape and grasp orientation representations during grasp planning and execution.…”
Section: Introductionmentioning
confidence: 99%